The effect of vitamin D supplementation on serum total 25(OH) levels and biochemical markers of skeletal muscles in runners - Aleksandra Żebrowska; Ewa Sadowska-Krępa; Arkadiusz Stanula; Zbigniew Waśkiewicz; Olga Łakomy; Eduard Bezuglov; Pantelis T. Nikolaidis; Thomas Rosemann; Beat Knechtle (Taylor & Francis Group, 2020)
Background The beneficial adaptation of skeletal muscle function to strenuous exercise is partially attributable to the improvement of vitamin D status. The present study aimed to evaluate the effects of a 3-week vitamin D supplementation on serum 25(OH)D levels and skeletal muscle biomarkers (i.e. troponin, myoglobin, creatine kinase and lactic dehydrogenase) of endurance runners. Methods A double-blind placebo-controlled study design was used and vitamin D supplementation was compared to a non-treatment control group. Twenty-four runners, competitors of the ultra-marathons held during the National Running Championships, were randomly assigned into two groups supplemented with the dose of 2000 IU vitamin D or placebo for three weeks. All subjects participated in three exercise protocols: (a) incremental exercise test (to determine the maximum oxygen uptake and the intensity of eccentric exercise), (b) eccentric exercise before and (c) after two dietary protocols. Venous blood samples were drawn at rest, immediately after the exercise and after 1 h and 24 h of recovery in order to estimate serum 25(OH)D levels, skeletal muscle biomarkers, proinflammatory cytokines and tumor necrosis factor-alpha (TNF-α) levels. A two-way ANOVA was used to test main effects and their interactions and Pearson correlation coefficients were analyzed to determine the effects of inter-variable relationships. Results Significant differences between pre- and post-intervention in baseline 25(OH)D levels were observed (34.9 ± 4.7 versus 40.3 ± 4.9 ng/ml, p = 0.02) in supplemented group. A higher post intervention 25(OH)D level was observed after vitamin D diet compared to placebo (40.3 ± 4.9 versus 31.8 ± 4.2 ng/mL, respectively; p < 0.05). The vitamin D supplementation decreased post-exercise (TN max) and 1 h post-exercise troponin (p = 0.004, p = 0.03, respectively), 1 h post-exercise myoglobin concentration (p = 0.01) and TNF-α levels(p < 0.03). 24 h post exercise creatine kinase activity was significantly lower in supplemented group compared to placebo (p < 0.05). A negative correlation was observed between post exercise 25(OH)D levels and myoglobin levels (r = − 0.57; p = 0.05), and 25(OH)D levels and TNFα (r = − 0.58; p = 0.05) in vitamin D supplemented group. Conclusions Three weeks of vitamin D supplementation had a positive effect on serum 25(OH)D levels in endurance trained runners and it caused a marked decrease in post-exercise biomarkers levels. We concluded that vitamin D supplementation might play an important role in prevention of skeletal muscle injuries following exercise with eccentric muscle contraction in athletes.